Assessment of Animal Welfare at an Exotic Animal Fair in Poland: A Focus on the Quality of Exhibition Containers for Reptiles and Amphibians - Damian Zieliński; Piotr Nawłatyna; Zofia Wójcik; Barbara Sobieszek; Arkadiusz Słaby; Martyna Nolewajka; Joanna Kapustka (Animals, 2024)
Given the growing number of events involving exotic animals, it is crucial to prioritize the well-being of the animals involved. This study aims to evaluate the quality of animal presentation at a selected fair in Poland and assess the level of animal welfare evident in the exhibition boxes, contributing to the ongoing dialogue on this important issue. The evaluators used a five-point Likert scale and a Yes/No system to analyze the living conditions during the fair, including the size of containers, presence of substrate, and environmental enrichment. They also assessed the occurrence of visual abnormal postures and behaviors to gauge the overall level of welfare. To ensure the reliability and consistency of the data and minimize potential bias, each evaluator repeated the rating process three times, with a three-week interval between each session. An average value was then calculated for each aspect. A total of 818 animals were present at the fair, with 688 being reptiles (84.11%) and 130 being amphibians (15.89%). This study revealed that the provision of substrate scored higher for reptiles compared to amphibians, while the size of containers for amphibians received higher ratings than those for reptiles. Visual abnormalities in posture and behavior were more common in reptiles than in amphibians. Display containers for snakes received the lowest ratings and showed more visual abnormalities in posture and behavior, raising concerns about their welfare. Despite the presence of environmental enrichment, the overall level of animal welfare was assessed as being medium/low. Pearson’s correlation coefficient indicated good reliability among the evaluators during the assessment process, with most assessments showing values > 0.8. Despite existing regulations for exhibitors, neglect remains prevalent. These findings highlight the potential negative impact of animal exposure at fairs on animal welfare. Display containers were often inadequately sized for the animals, particularly for snakes, chameleons, monitor lizards, and salamanders.